Mapping Higher Order Thinking Skills of Prospective Primary School Teachers in Facing Society 5.0 - Dini Ramadhani; Ary Kiswanto Kenedi; Yullys Helsa; Ciptro Handrianto; Muhammad Rizki Wardana (Al Ibtida: Jurnal Pendidikan Guru MI, 2021)
AbstractThe need to develop higher order thinking skills (HOTS) for prospective primary school teachers in facing society 5.0 has been motivating this research. This development process requires valid data regarding the HOTS description of prospective primary school teachers. The research is aimed to determine the HOTS ability of prospective primary school teachers in facing society 5.0. This is a qualitative descriptive study involving 125 senior students in the department of primary school teacher education. The data collection instrument utilized the validated mathematical HOTS test questions. The resulting score is then converted to an ideal score and mapped. The average score attained by prospective primary school teacher students was 57.01, according to the findings. This score indicates that prospective teachers' HOTS ability is in the fairly good category. The findings of this study can be used to improve HOTS for future teachers.Keywords: HOTS, prospective primary school teacher, mathematics.Â AbstrakPenelitian ini dilatarbelakangi pentingnya pengembangan HOTS calon guru sekolah dasar (SD) dalam menghadapi era society 5.0. Proses pengembangan ini diperlukan data valid mengenai gambaran HOTS calon guru SD. Tujuan penelitian ini adalah untuk menggambarkan kemampuan HOTS calon guru SD pada pembelajaran matematika dalam menghadapi era society 5.0. Penelitian ini merupakan penelitian deskriptif kualitatitif dengan melibatkan sebanyak 125 mahasiwa akhir di jurusan pendidikan guru sekolah dasar. Instrumen pengumpulan data menggunakan soal test HOTS matematis yang telah divalidasi. Skor yang didapatkan kemudian di tranformasi ke skor ideal dan kemudian dipetakan. Hasil penelitian menunjukkan bahwa skor rata-rata yang diperoleh oleh mahasiswa calon guru SD adalah 57,01. Skor ini membuktikan bahwa kemampuan HOTS mahasiswa calon guru berada pada kategori cukup baik. Implikasi penelitian ini dapat dijadikan landasan dalam pengembangan HOTS calon guru ke depan.Kata kunci: HOTS, calon guru SD, matematika.